Profile of Patients with Dermatophytosis at the Dermatology and Venereology Outpatient Clinic of RSUD Bali Mandara, 2023–2025 - Made Hendra Setiawan; I Made Birawan (Jurnal Kesehatan dan Kedokteran, 2026)
Dermatophyte infection is a superficial fungal infection that affects keratinized tissues such as the skin, hair, and nails. The warm and humid tropical climate in Indonesia contributes to the high prevalence of dermatophytosis, making it a significant dermatological health concern. Objective: This study aimed to describe the profile of dermatophyte infections based on age, sex, type of dermatophytosis according to infection site, and the therapies administered to patients at the Dermatology Outpatient Clinic of RSUD Bali Mandara from January 2023 to December 2025. Methodology: A retrospective descriptive study was conducted using medical record data of patients diagnosed with dermatophyte infections at RSUD Bali Mandara. Variables analyzed included age, sex, type of tinea, and treatment provided. Findings: Among 117 dermatophytosis patients, the majority were female (54.5%), and the 45–64-year age group was the most affected (33.33%). Tinea corporis was the most common type of dermatophytosis (47.32%), and topical therapy was the most frequently administered treatment (76.1%). Implications: These findings provide a basis for further research and support clinical decision-making and health policy development in dermatology, particularly regarding the prevention and management of dermatophytosis. Originality: This study presents up-to-date data on the profile of dermatophyte infections at RSUD Bali Mandara, offering specific local information for the 2023–2025 period that has been previously underreported.